INVESTMENT OPPORTUNITY SET, DIVIDEND POLICY AND CORPORATE VALUE: EVIDENCE FROM TRADE, SERVICES AND INVESTMENT SECTOR OF INDONESIA STOCK EXCHANGE - Nugraha, Jaka (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2019)
The purpose of this paper is to investigate influences the proxy of investment opportunity set and dividend policy on corporate value. This study is tested with a sample of trade, services and investment sector in Indonesia Stock Exchange which is contained 72 companies covering a 3-years period from 2009 to 2011. Structural equation modeling with Partial Least Square is used in this study. This paper found a significantly positive influence between the proxies of investment opportunity set on dividend policy. In addition, there is a significantly positive influence between the proxies of dividend policy on corporate value. The result had consistently with informational content of dividend that explained that dividend paid was considered to be companies prospect in the future. This result also supported signaling theory that emphasize dividend paid is a signal on the market. The result also revealed a significantly positive influence between the proxies of investment opportunity set on corporate value. This result has supporting and consistently with research result by Fama (1978). Direct effect from investment decision on corporate value is results obtained of investment activity itself.